PERBANDINGAN RESPON RATE KETAMIN 0,25 MG/ KG. BB IV DENGAN PETHIDIN 25 MG IV UNTUK MENGATASI SHIVERING PADA SEKSIO SESARIA DENGAN ANESTESI SPINAL - , AYU ESTI SUNYOTO; , Dr. Muhdar Abubakar, SpAn, K, ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Shivering is very unpleasant and physiologically stressful for patient. Patients report that accompanying cold sensation worse than surgical pain. It may also cause complication, especially in patient with coronary artery disease, because of associated increases in oxygen consumption by 100-600%, increases in carbon dioxide production, cardiac output, catecolamine, and heart rate, decreases in minute ventilation and mixed venous oxygen saturation. Moreover, an increase in intracranial and intraocular pressure, interference with monitoring of ECG, pulse oximetry and blood pressure, increased metabolic rate and lactic acidosis. Various drugs have been investigated for treatment of shivering including pethidine and ketamine. Aim : The aim of this study was to compare the response rate of ketamine 0,25 mg/kgBB with pethidine 25 mg to control shivering during Cesarean Section under spinal anestesia. Design : This is a randomized double blind controlled study. Subjects : Subjects are 124 female patients undergoing Cesarean Section with spinal anestesia who fullfill inclusion and exclusion criteria. Intervention : Patients were randomly alocated into two groups, either consist of 62 patiens. Group P received 25 mg of pethidine and group K received ketamine 0,25mg/kgBW. Result : The results showed that the measurement of minute-1, 2, 3 there were response rate significant differences in both study groups (p <0.05), the response rate is negative at 25 mg iv pethidin group occurred at minute-1 were 62 patients (100%), the 2nd minute of 60 patients (96.8%), and the 3rd minute as many as 16 patients (25.8%), whereas in the ketamine group negative response rate occurred at minute-1 total of 12 patients (19, 4%). In the 2nd minute 100% positive response rate occurred in the ketamine group. While the group pethidin, 100% positive response rate occurred in the 4th minute. Ketamine 0.25 mg / kg iv can be overcome shivering in 2 minutes (1.19 Â± 0.40 min) and shivering recurrence occurred in 27.4% patients after 17.35 minutes. While pethidin 25 mg iv can be overcome shivering in 4 minutes (3.23 Â± 0.49 min) and shivering recurrence occurred in 8.1% of patients after 30 minutes. Side effects include nausea in the ketamine group 8.1%, while pethidin 21%, dizziness side effects for ketamine group 25.8%, whereas 16.1% pethidin. Statistically both shivering recurrence and nausea between the two groups showed significant differences (p <0.05). Conclusion: Response rate in the administration of ketamine 0.25 mg / kg intravenously better than pethidin 25 mg intravenously to control shivering during Cesarean Section under spinal anestesia.